Proyecto de valoración financiera de la elaboración y comercialización de pulpa de araza para la ciudad de Guayaquil - Salazar Bohórquez, Rosa Lissette (2010)
The study presented below indicates the feasibility of production and marketing of pulp arazá in the city of Guayaquil. Since in this city is currently not the fruit. Allowing us to be pioneers in the distribution of what we call "ARAZA-PULPA" It is important to inform the community the main features and benefits with which arazá account, as well as being a man rich fruit on the palate enjoys great benefits important proteins and vitamins which makes it attractive to our potential consumers.